Molecular and functional properties of psychrophilic elongation factor G from the antarctic eubacterium Pseudoalteromonas haloplanktis TAC 125 - RGGIERO I; PALMA M; MASULLO M.; RAIMO, GENNARO; ARCARI, PAOLO (Springer-Verlag Tokyo:3 3 13 Hongo Bunkyo-Ku, Tokyo 113-0033 Japan:011 81 3 38120703, Fax: 011 81 3 38124644, 2007)
The molecular and functional properties of the elongation factor (EF) G from the psychrophilic Antarctic eubacterium Pseudoalteromonas haloplanktis (Ph) were studied. PhEF-G catalyzed protein synthesis in vitro that was inhibited by fusidic acid, an antibiotic specifically acting on EF-G. The EF interacted with GDP only in the presence of P. haloplanktis ribosome and fusidic acid with an affinity similar to that displayed by Escherichia coli EF-G. The psychrophilic translocase elicited a ribosome-dependent GTPase that was competitively inhibited by GDP, the slowly hydrolyzable GTP analog GppNHp, and the protein synthesis inhibitor ppGDP. The temperature dependence of the activity of PhEF-G reached its maximum at least 26 degrees C beyond the growth temperature of P. haloplanktis (4-20 degrees C). The heat inactivation profile of the ribosome-dependent GTPase of PhEF-G gave a temperature for half inactivation (46 degrees C), significantly lower than that for half denaturation measured by either UV- (57 degrees C) or fluorescence-melting (62 degrees C). This finding was attributed to a different effect of the temperature on the catalytic domain with respect to that elicited on the other domains constituting the EF, thus confirming the differential molecular flexibility present in psychrophilic enzymes. A molecular model, based on the 3D coordinates of a thermophilic EF-G, showed differences only in connecting loops.